Adverse drug reaction profile and prescription pattern of antihypertensive drug monotherapy at tertiary care hospital Nepalgunj, Nepal - Neupane, Ganesh Prasad; Rai, Maya (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Hypertension is the leading cause of morbidity and mortality worldwide which requires long term therapy to prevent complication associated with it. As drugs are used for longer duration it is necessary to know potential undesirable effects for making the appropriate choice. Aim and objective of the study was to monitor the adverse drug reactions (ADRs) and to know prescribing pattern of antihypertensive monotherapy. Methods: The present work was an open, non-comparative, observational study conducted on seventy-three (73) hypertensive patients who were prescribed single antihypertensive drug at medical OPD of Nepalgunj Medical college by conducting patient interviews, recording the data on ADR monitoring form. Results: Calcium channel blockers were found to be the most frequently associated drugs with adverse drug reactions (n=12), followed by diuretics (n= 6), Angiotensin converting enzyme inhibitors (n=3), β-blockers (n= 2) and Angiotensin receptor blocker (n=1). Among individual drugs, amlodipine was found to be the commonest drug associated with adverse drug reactions (n = 10). On analysis of prescription pattern again amlodipine was most commonly prescribed antihypertensive monotherapy followed by hydrochlorothiazide. Conclusions:Amlodipine was most commonly associated with ADRs and it was also most commonly prescribed antihypertensive drugs as monotherapy. The above findings would be useful for physicians in rational prescribing.